Pengaruh Desain Produk Dan Citra Merek Terhadap Keputusan Pembelian Konsumen Pada CV. Graha Mineral Sibolga - Rani Aulia Sihombing; Hadijah Sipahutar; Nelly A.Sinaga (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to determine the effect of product design and brand image on consumer purchasing decisions at CV. Graha Mineral Sibolga. The type of research used is a quantitative research method with a correlational study approach. The sample in this research is the customer of CV. Graha Mineral Sibolga by distributing questionnaires totaling 44 respondents. Based on the results of the research it is known that the value of the calculation of the coefficient of determination obtained a number of 97.7%, this means that what occurs in the variation of the dependent variable (purchasing decision) of 97.7% is determined by the independent variables (product design and brand image) and the remainder is 2.3% influenced by other variable factors. Based on the results of the multiple linear regression test, the results were obtained: Y = 2.488 + 0.170X1 + 0.764X2. The constant value is positive, indicating a positive influence on the independent variable, where the Purchase Decision Variable is 2.488 units. The Product Design Variable (X1) has a regression coefficient of 0.170, has a positive influence on purchasing decisions (Y) and Brand Image variable (X2) has a regression coefficient of 0.764, has a positive influence on purchasing decisions (Y). From the results of the Hypothesis Test Test t (perial) t_count 2.617 > t_table 2.020 then Ha is accepted and H0 is rejected, which partially states variable X1 has a positive effect on variable Y. And obtained t_count 10.515> t_table 2.020 then Ha is accepted and H0 is rejected, which partially states that variable X2 has a positive effect on variable Y. While the results of the Hypothesis Test F Test (Simultaneous) show that the F_count value is 880,883 > F_table 3.22, then Ha is accepted and H0 is rejected which states simultaneously Product Design and Brand Image have a positive effect on purchasing decisions at CV.